2006
DOI: 10.1086/510562
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding Sequential Innovators: Prizes, Patents, and Buyouts

Abstract: This paper presents a model of cumulative innovation where firms are heterogeneous in their research ability. We study the optimal reward policy when the quality of the ideas and their subsequent development effort are private information. The optimal assignment of property rights must counterbalance the incentives of current and future innovators. The resulting mechanism resembles a menu of patents that have infinite duration and fixed scope, where the latter increases in the value of the idea. Finally, we pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…The resulting increase in R&D could lead to a substantial increase in consumption. 19 For example, Comin (2004) considers that a reasonable markup in these industries should be around 1.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting increase in R&D could lead to a substantial increase in consumption. 19 For example, Comin (2004) considers that a reasonable markup in these industries should be around 1.5.…”
Section: Resultsmentioning
confidence: 99%
“…In patent-protected and R&D-intensive industries, the markup and the profit share should be much larger. 19 Finally, the numerical analysis is performed on a semi-endogenous growth model, in which increasing R&D investment has no effect on long-run growth. In the case of a fully endogenous-growth model, raising R&D through the elimination of blocking patents would increase the long-run growth rate of consumption.…”
Section: Dynamic Distortionmentioning
confidence: 99%
“…Their data involved eight innovative firms from different fields and the study results indicate that understanding SME behavior and innovation creation involves a mixture of coping with commonly recognized elements on funding problems (consistency of finance), research management, human resources (staff turnover and production skills), logistics and marketing. Accordingly, economists (Nalebuff & Stiglitz, 1983;Wright, 1983;Rogerson, 1989) have long claimed that under certain conditions innovation prizes can induce innovation, that is, provide private entrepreneurs with strong incentives to invest in R&D. In particular, the interest has been in innovation prizes as an alternative to patent systems in invention appropriation (de Laat, 1996;Scotchmer, 2004;Masters, 2005;Hopenhayn, Llobet & Mitchell, 2006;Chari, Golosov & Tsyvinski, 2012;Clancy & Moschini, 2013). What literature there is on innovation awards has, however, been mainly confined to studies concerning the innovativeness of (public) management (Altshuler & Behn, 1997;Bernier & Hafsi, 2007;Borins, 2008) instead of the realm of technological innovation, where the majority of innovation studies are found (Kalil, 2006).…”
Section: Foundations: Innovation Policy As Context For Awardsmentioning
confidence: 99%
“…This phenomenon of "standing on the shoulders of giants" became to interest scholars studying the optimal patent breadth, the optimal division of profit between inventors, and antitrust issues in research activities (e.g. Scotchmer 1991;Hopenhayn et al 2006). The idea of cumulative research or sequential innovation, an issue which, as we have seen, was noted by Marshall, has gained deserved interest.…”
Section: Invention Innovation and Technological Changementioning
confidence: 99%